Pengaruh Modernitas dan Gaya Hidup terhadap Perilaku Konsumsi Mahasiswa - Astuti, Ratna Fitri; Ulfah, Maria; Ellyawati, Noor (Universitas Pendidikan Ganesha, 2022)
Consumption choices no longer show the ability to distinguish between basic needs, urgent needs, and non-essential needs. The consumption behavior of modern society itself is then associated with modernity and lifestyle. This study uses a descriptive type of research with a quantitative approach. The number of samples used was 60, obtained by distributing questionnaires. Data analysis using multiple linear regression analysis technique. Based on the results of the study, it is known that modernity and lifestyle affect consumption behavior. In this study, modernity's effect on consumption behavior can be seen when students prioritize their minds over their emotional opinions. Lifestyle in this study can be seen from the routine activities carried out, where students can determine priorities to meet needs in daily activities. This shows that the modernity and lifestyle of students in consumption behavior can be seen from how students make purchases of an item. Students prioritize their minds compared to their emotional opinions, while the lifestyle of students when carrying out daily activities in meeting their needs is shown by their consumption behavior by adjusting their needs and desires.